Waveguide features in self-patternable amine functionalized organic-inorganic hybrids - Sá Ferreira, R. A.; André, P. S.; Nogueira, R.; Vicente, C.; Macedo, A. G.; Maia, L. J Q [UNESP]; Carlos, L. D.; Ribeiro, Sidney José Lima [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2007)
We report the use of organic-inorganic sol-gel derived poly(oxyehylene)/ siloxane hybrid doped with methacrylic acid modified zirconium (IV) n-propoxide for the fabrication of low cost waveguides trough direct UV laser writing. The organic-inorganic hybrids were processed as monoliths with size and shape control. The effective guiding region was identified and the number of modes was estimated via mode field analyses. A grating was successfully superimposed on the channel and the respective reflection spectrum was measured, enabling the determination of the guiding region dimension, the calculation of the effective refractive index of the guided mode. © 2007 IEEE.
Keywords: Gratings; Integrated optics; Optical waveguide components; Acids; Amines; Electromagnetic waves; Gelation; Optical properties; Organic compounds; Photonics; Refractive index; Sol-gels; Waveguides; Zirconium; Organic-inorganic hybrids; Colloids